1977
DOI: 10.1017/s0043174500033063
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Translocation of Nitrofen and Oxyfluorfen

Abstract: The site of uptake of nitrofen (2,4-dichlorophenyl-p-nitrophenyl ether) and oxyfluorfen [2-chloro-1-(3-ethoxy-4-nitrophenoxy)-4-(trifluoromethyl)benzene] was studied using a double pot technique. Sorghum [Sorghum bicolor(L.) Moench ‘RS610′] and pea (Pisum sativumL. ‘Alaska’) were the test plants. Herbicidal activity measured by the reduction in fresh weight of the roots and shoots of treated plants showed that exposure of the shoot zone to the herbicides caused much more injury to the plants than root exposure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

1979
1979
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 11 publications
1
12
0
Order By: Relevance
“…Horseweed counts from sunrise applications (34%) were not different from sunset or midday applications (4% and 75%, respectively); however, sunset applications were more efficacious than applications at midday. Although the majority of application TOD research has indicated that POST herbicide control is generally greater when the herbicide is applied in the middle portion of the day (Doran and Andersen 1976; Martinson et al 2002; Miller et al 2003; Peterson and Al-Khatib 1999; Stewart et al 2009; Stopps et al 2013), some research suggests that this conclusion may not be accurate for all herbicides (Fadayomi and Warren 1977; Lee and Oliver 1982; William and Warren 1975). William and Warren (1975) found that nitrofen was more efficacious on purple nutsedge ( Cyperus rotundus L.) when applied at night rather than during the day, and Fadayomi and Warren (1977) later determined that this increase in efficacy resulted from an increase in herbicide absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Horseweed counts from sunrise applications (34%) were not different from sunset or midday applications (4% and 75%, respectively); however, sunset applications were more efficacious than applications at midday. Although the majority of application TOD research has indicated that POST herbicide control is generally greater when the herbicide is applied in the middle portion of the day (Doran and Andersen 1976; Martinson et al 2002; Miller et al 2003; Peterson and Al-Khatib 1999; Stewart et al 2009; Stopps et al 2013), some research suggests that this conclusion may not be accurate for all herbicides (Fadayomi and Warren 1977; Lee and Oliver 1982; William and Warren 1975). William and Warren (1975) found that nitrofen was more efficacious on purple nutsedge ( Cyperus rotundus L.) when applied at night rather than during the day, and Fadayomi and Warren (1977) later determined that this increase in efficacy resulted from an increase in herbicide absorption.…”
Section: Resultsmentioning
confidence: 99%
“…Oxyfluorfen reduces the content of chloroplasts in the cells of the assimilation parenchyma of leaves, and this has an adverse effect on the biochemical and physiological processes in plants (2,4,7,8,9,16,17). The photosynthesis, transpiration, and gas exchange disruptions are expressed in delayed plant growth and development, and frequently, this is a contributing factor to plant death (1,3,5,6,10,11,12,13,14,15,17).…”
Section: Introductionmentioning
confidence: 99%
“…Protox-inhibiting herbicides are absorbed by root (soil-applied) and leaf tissue (foliar-applied), but have limited translocation (Fadayomi and Warren 1977;Ritter and Coble 1981a;Unland et al 1999). Ritter and Coble (1981b) showed that translocation of acifluorfen is also dependent on temperature and relative humidity.…”
Section: Introductionmentioning
confidence: 99%